Exploring the Use of Folktale to Foster English Learning Skills : A Qualitative Perspective - Miftahul Jannah; Darmawan Darmawan; Desrin Lebagi; Wahyudin Wahyudin (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to explore the use of folktales in enhancing English language skills among junior high school students within an EFL context. Employing a qualitative descriptive method, data were collected through interviews with one English teacher and five ninth-grade students at SMP Negeri 12 Palu, as well as document analysis of an English textbook. The findings reveal that folktales contribute to the development of language skills by increasing student motivation, reducing anxiety, and providing meaningful language input. Folktales were also found to be strategically integrated into textbook activities aligned with curriculum objectives. It is concluded that folktales represent an effective, culturally responsive medium for fostering English language learning.